2010
DOI: 10.1590/s0101-98802010000300001
|View full text |Cite
|
Sign up to set email alerts
|

Videocirurgia no manejo da doença de Crohn intestinal

Abstract: RESUMO: A doença de Crohn é uma moléstia com um amplo espectro de manifestações. Seu tratamento é complexo e freqüentemente os pacientes portadores desta afecção necessitam de intervenções cirúrgicas. Com o surgimento da laparoscopia e sua popularização no tratamento das afecções intestinais, demonstrando resultados superiores ao acesso convencional e quebrando paradigmas como sua utilização no tratamento do câncer colorretal, passou-se a cogitar se esse acesso seria indicado também nas doenças inflamatórias i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…It is estimated that approximately 70 to 90% of patients will require some form of surgical treatment throughout their lifetime. 1,2 The role of laparoscopic surgery in the management of colorectal diseases is well established, with numerous benefits in both benign and oncologic resections. 3 However, laparoscopic surgery in CD has been shown to be challenging due to the inflammatory, transmural and recurrent characteristics of this condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that approximately 70 to 90% of patients will require some form of surgical treatment throughout their lifetime. 1,2 The role of laparoscopic surgery in the management of colorectal diseases is well established, with numerous benefits in both benign and oncologic resections. 3 However, laparoscopic surgery in CD has been shown to be challenging due to the inflammatory, transmural and recurrent characteristics of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The presence of active inflammation, mes-entery infiltration and friability, presence of fistulae, adhesions and concomitant immunosuppression can significantly complicate a procedure that already has intrinsic difficulties even when using the conventional approach. 2,6 In spite of these characteristics, laparoscopic surgery has been increasingly performed in the management of CD, especially in primary ileocolic disease. 7 Recent studies have demonstrated that this is a feasible, safe, effective procedure, which shows benefits in postoperative recovery, even in the presence of abscesses and intestinal fistulae.…”
Section: Introductionmentioning
confidence: 99%